ADR & the law : a report of the American Arbitration Association, the Fordham International Law Journal and the Fordham Urban Law Journal - American Arbitration Association; American Arbitration Association ([New York, N.Y.?] : American Arbitration Association, 1997)
Includes indexes
Description based on: 1997 ed.; title from cover
1997 ed. cover developments in ADR 1994-1996
Keywords: Dispute resolution (Law) -- United States -- Periodicals; Arbitration, Industrial -- United States -- Periodicals; Arbitration (International law) -- Periodicals; Arbitration and award -- United States -- Periodicals